An Algorithm of Micromouse Maze Solving - Jianping Cai; Xuting Wan; Meimei Huo; Jianzhong Wu (2010 IEEE 10th International Conference on Computer and Information Technology, 2010)
This paper proposes a maze exploring algorithm named "Partition-central Algorithm", which is used to find the shortest path in a micromouse competition maze. A standard 16*16 units maze is divided into 12 partitions in this algorithm. Depending on the absolute direction of the micromouse and the locations of each partition, exploring rules alter when the micromouse walks to optimize the maze exploring process. A simulation program is developed to verify the algorithm. The test result shows that Partition-central algorithm has higher average efficiency when compared with other algorithms.